IMPACT OF COVID-19 ON TOURISM INDUSTRY IN TAMILNADU - K, SASIREKHA; SANKAR, Dr.P. (The journal of contemporary issues in business and government, 2021)
The outbreak of the pandemic brought the entire world to a complete stand-still and created major disruptions in the lives of people globally. It also adversely affected the global economy resulting in large scale job losses. Out of all the industries that suffered, the travel and tourism industry was impacted the most owing to the lockdown and travel restrictions. As per a report by the World Travel and Tourism Council (WTCC), COVID-19 has caused the tourism industry almost USD 22 billion and a loss of almost 50 million jobs worldwide.